Using video conferencing applications to share the death experience during the COVID-19 pandemic (2020)
Due to isolation and social distancing to maintain patient and staff safety during the COVID-19 pandemic, an alternative to face-to-face interaction was needed. Nurses facilitated critical patient-family communication. Video conferencing applications aided socially distanced families to connect with dying loved ones. This article will explore the use of these popular apps.